A barium sulfate@aluminum borate-Mxene composite powder and its preparation method

CN122501903APending Publication Date: 2026-08-04JIANGXI GUANGYUAN CHEM +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610688707.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-19
Publication Date
2026-08-04

AI Technical Summary

Technical Problem

[0005]针对现有技术中单一填料难以同时显著提升聚合物基复合材料力学性能与阻燃性能,以及MXene二维材料易堆叠、与无机填料界面结合弱的问题,本发明提供一种硫酸钡@硼酸铝/Mxene复合粉体及其制备方法

Benefits of technology

[0024] Structural Innovation and Synergistic Effect: This invention pioneers a multi-level composite structure consisting of a rigid barium sulfate core, a high-temperature resistant and flame-retardant aluminum borate shell, and flexible MXene sheets. This structure is not a simple stacking of components, but rather achieved through ingenious design.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a barium sulfate@aluminum borate-MXene composite powder and its preparation method, belonging to the technical field of high-performance inorganic composite functional materials. The composite powder possesses a unique core-shell-lamellar structure: barium sulfate nanospheres form the core, coated with a uniform aluminum borate layer to form the core-shell nanospheres. These barium sulfate@aluminum borate core-shell nanospheres are further loaded onto the surface of two-dimensional MXene nanosheets. The preparation method includes: synthesizing barium sulfate nanospheres via precipitation; in-situ coating of aluminum borate onto their surface using a hydrothermal method to form a barium sulfate@aluminum borate core-shell structure; preparing MXene nanosheets via liquid-phase exfoliation; and finally mixing and assembling the two to obtain the final product. The core advantage of this invention lies in achieving a triple synergy of high-temperature flame retardancy of aluminum borate, rigid support of barium sulfate, and interface enhancement and barrier effect of MXene through the above-mentioned multi-level structural design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance inorganic composite materials technology, specifically to a barium sulfate@aluminum borate-Mxene composite powder and its preparation method. Background Technology

[0002] In aerospace, transportation, and high-end equipment manufacturing, stringent requirements are placed on the stability, lightweight, and multifunctionality of materials under extreme environments (such as high temperature and high load). Developing composite powders that combine high hardness, low thermal conductivity, good chemical stability, and interfacial reinforcement effects is key to preparing next-generation high-performance composite materials.

[0003] Barium sulfate (BaSO4) possesses high density, high hardness, chemical inertness, and good thermal stability, making it an ideal rigid core material. However, its surface inertness leads to weak interfacial bonding with many matrices. Therefore, researchers often coat its surface with functional shells. Aluminum borate (such as 9Al2O3·2B2O3) is an important class of ceramic materials, renowned for its excellent high-temperature stability, low thermal conductivity, high hardness, and good wear resistance. Coating it onto the surface of barium sulfate, forming a barium sulfate@aluminum borate core-shell structure, not only utilizes the core support of barium sulfate but also significantly improves the overall temperature resistance, thermal insulation, and mechanical properties of the composite particles. However, such pure ceramic core-shell particles have limited capabilities in electrical and thermal conductivity or imparting special functions to polymer matrices. MXene (such as Ti3C2T...) x MXene nanosheets are a class of two-dimensional materials with high electrical conductivity, good mechanical strength, and rich surface chemistry. Introducing them into composite material systems holds promise for endowing materials with electrical conductivity, thermal conductivity, or special interfacial functions. However, MXene nanosheets are easily oxidized at high temperatures, and the interfacial bonding mode and synergistic reinforcement mechanism with ceramic particles remain unclear. How to stably composite brittle ceramic particles with two-dimensional sheet-like MXene to construct a heterostructure with strong interfacial bonding is a key challenge in improving the overall performance of composite materials.

[0004] Currently, barium sulfate is mainly used as a filler in plastics, paper, coatings, and paints, while research on aluminum borate materials focuses on the preparation and application of its bulk ceramic or whisker forms. Research on combining barium sulfate and aluminum borate to form barium sulfate@aluminum borate core-shell nanospheres is relatively limited. Furthermore, research on combining barium sulfate@aluminum borate with two-dimensional MXene has not been reported. Existing technologies lack a structural design and preparation method that organically combines the rigidity of barium sulfate, the high-temperature insulation properties of aluminum borate, and the interfacial functionalization advantages of MXene. Therefore, this invention aims to provide a novel barium sulfate@aluminum borate / MXene composite powder. By constructing a multi-level structure of "hard core-ceramic shell-functional layers," it overcomes the performance limitations of single materials and meets the demand for multifunctional fillers in high-end composite materials. Summary of the Invention

[0005] To address the limitations of existing technologies where a single filler cannot simultaneously and significantly improve the mechanical and flame-retardant properties of polymer-based composite materials, and the problems of MXene two-dimensional materials being prone to stacking and having weak interfacial bonding with inorganic fillers, this invention provides a barium sulfate@aluminum borate / MXene composite powder and its preparation method. Specifically, this invention aims to provide a composite powder with a specific "core-shell-lamellae" multi-level structure, which achieves a highly efficient synergy between the high-temperature flame-retardant properties of aluminum borate, the rigid support properties of barium sulfate, and the interfacial reinforcement and barrier properties of MXene.

[0006] A controllable preparation method for the aforementioned composite powder is provided. Through stepwise synthesis and in-situ assembly, a uniform core-shell structure and strong interfacial bonding are ensured, overcoming the defects of simple physical mixing. This composite powder is then applied as a multifunctional filler to a polymer matrix, aiming to simultaneously and significantly improve the tensile strength, flexural strength, and impact toughness of the composite material, while also endowing it with efficient synergistic flame-retardant effects of the gas and condensed phases, thus overcoming the technical bottleneck of traditional fillers having only a single function.

[0007] A barium sulfate@aluminum borate-Mxene composite powder is disclosed, wherein the composite powder has a core-shell-lamellar composite structure; wherein barium sulfate nanospheres constitute the core, and aluminum borate layers are uniformly coated on the surface of the barium sulfate nanospheres to form a core-shell structure of barium sulfate@aluminum borate nanospheres; the barium sulfate@aluminum borate nanospheres are uniformly deposited and fixed on the surface of two-dimensional layered Mxene nanosheets.

[0008] Preferably, the barium sulfate nanospheres have a particle size of 80-200 nm.

[0009] Preferably, the thickness of the aluminum borate layer is 5-20 nm.

[0010] Preferably, the Mxene nanosheets are Ti3C2T. x Its thickness is 1-10 nm, and the planar size of the sheet is 0.5-5 μm.

[0011] Preferably, the Ti3C2T x T in x It is one or more of the surface terminating groups of -OH, -O, -F or -Cl.

[0012] This invention also provides a method for preparing barium sulfate@aluminum borate-Mxene composite powder, comprising the following steps:

[0013] S1. Barium sulfate nanospheres were synthesized using a precipitation method;

[0014] S2. Disperse the barium sulfate nanospheres obtained in step S1 in a solvent, add an aluminum source and a boron source, and coat the surface of the barium sulfate nanospheres with an aluminum borate layer through in-situ reaction to obtain barium sulfate@aluminum borate core-shell nanospheres.

[0015] S3. Provides Ti3C2T prepared by liquid phase exfoliation. x Nanosheet dispersion, the Ti3C2T x The nanosheets have a thickness of 1-10 nm and a planar size of 0.5-5 μm.

[0016] S4. Combine the barium sulfate@aluminum borate core-shell nanospheres obtained in step S2 with the Ti3C2T nanospheres obtained in step S3. x The nanosheet dispersion was mixed to deposit and immobilize the barium sulfate@aluminum borate nanospheres on Ti3C2T. x The surface of the nanosheets was subjected to solid-liquid separation and drying to obtain the barium sulfate@aluminum borate / Mxene composite powder.

[0017] Preferably, in step S2, the aluminum source is aluminum nitrate, aluminum chloride, or aluminum isopropoxide; and the boron source is boric acid, boron oxide, or sodium borate.

[0018] Preferably, in step S2, the in-situ reaction is a hydrothermal method or a sol-gel method, the reaction temperature is 120-200℃, and the reaction time is 2-24 hours.

[0019] Preferably, in step S3, the liquid phase stripping method includes: reacting Ti3AlC2 powder in an acidic etching solution containing fluoride to selectively etch away the aluminum layer, thereby obtaining a multilayer Ti3C2T x Subsequently, the multilayer Ti3C2T x The Ti3C2T was obtained by intercalation and exfoliation in a polar solvent. x Nanosheet dispersion.

[0020] Preferably, the acidic etching solution containing fluoride is an aqueous solution of hydrofluoric acid, a mixed solution of lithium fluoride and hydrochloric acid, or an aqueous solution of ammonium fluoride; the polar solvent is water, N,N-dimethylformamide, isopropanol, or propanol.

[0021] In step S4, the barium sulfate@aluminum borate core-shell nanospheres and Ti3C2T x The mass ratio of the nanosheets is 1:10 to 10:1; the mixing method is stirring, ultrasonication, or a combination of both.

[0022] The prepared composite powder is used in high-temperature resistant thermal insulation materials, wear-resistant composite materials, reinforced polymer-based composite materials, or flame-retardant composite materials.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] Structural Innovation and Synergistic Effect: This invention pioneers a multi-level composite structure consisting of a rigid barium sulfate core, a high-temperature resistant and flame-retardant aluminum borate shell, and flexible MXene sheets. This structure is not a simple stacking of components, but rather achieved through ingenious design.

[0025] Synergistic mechanical enhancement: The rigid core-shell spheres serve as the main load-bearing points, effectively dispersing stress; the MXene sheets act as a two-dimensional reinforcing network, bridging and transferring loads, while simultaneously forming a strong interfacial bond with the polymer through their large specific surface area, jointly preventing crack propagation, thereby achieving a simultaneous and significant improvement in both strength and toughness.

[0026] Synergistic flame-retardant function: During combustion, the aluminum borate shell melts first to form a dense and stable glassy ceramic barrier, covering the material surface; MXene sheets are stacked layer by layer in the matrix to form a physical barrier layer, delaying the diffusion of pyrolysis products and oxygen; and the barium sulfate core plays a role in stabilizing the char layer skeleton. The three play flame-retardant roles in the gas phase and condensed phase respectively, producing a highly efficient synergistic flame-retardant effect of "1+1+1>3".

[0027] Significant performance improvement: Experimental data shows that adding only 3 wt% of the composite powder of this invention can increase the tensile strength and impact strength of epoxy resin-based composite materials by more than 40%, while reducing the peak heat release rate by more than 30% and increasing the char residue to more than 22%. This simultaneous and substantial optimization of mechanical and flame-retardant properties cannot be achieved using a single filler or physical mixture.

[0028] Controllable process and excellent interface: This invention employs a stepwise synthesis and in-situ assembly strategy, achieving effective control over the core-shell thickness, MXene size, and the final composite structure. Through a chemically driven assembly process, a strong interfacial bond is formed between the core-shell spheres and the MXene sheets, ensuring efficient stress transfer and effective functional synergy, while avoiding the weak interface and filler agglomeration problems caused by physical mixing.

[0029] Broad application prospects: As a highly efficient and multifunctional filler, this composite powder can be widely used in fields with stringent requirements for lightweight, high strength, and high safety, such as new energy vehicle parts, aerospace interior materials, high-end electronic packaging materials, and building fireproof coatings, etc., and has huge market potential and application value. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0031] Example 1

[0032] Barium sulfate@aluminum borate / Ti3C2T x Preparation of composite powder (BAB / Mxene)

[0033] 1. Synthesis of Barium Sulfate Nanospheres: 0.02 mol of barium chloride (BaCl2·2H2O) and 0.4 g of polyvinylpyrrolidone (PVP, M) were synthesized. w = 40000) was dissolved in 200 mL of deionized water and magnetically stirred to form solution A. 0.02 mol sodium sulfate (Na₂SO₄) was dissolved in 200 mL of deionized water to form solution B. At room temperature, solution B was added dropwise to the vigorously stirred solution A at a rate of 5 mL / min. After the addition was complete, the reaction continued for 2 hours. The resulting white suspension was centrifuged, washed three times with deionized water, washed once with ethanol, and then vacuum dried at 60 °C for 12 hours to obtain barium sulfate nanospheres with an average particle size of approximately 150 nm.

[0034] 2. Preparation of Barium Sulfate@Aluminum Borate Core-Shell Nanospheres

[0035] 0.5 g of the above barium sulfate nanospheres were ultrasonically dispersed in 80 mL of deionized water. 0.02 mol of aluminum nitrate (Al(NO3)3·9H2O) and 0.0044 mol of boric acid (H3BO3) were added sequentially, and the mixture was stirred continuously for 1 hour to ensure thorough mixing. The pH of the solution was adjusted to 9.0 with ammonia. The mixed suspension was transferred to a 100 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene and reacted at 180 °C for 12 hours. After the reaction was completed, the mixture was allowed to cool naturally. The product was centrifuged, washed, and dried to obtain core-shell structured barium sulfate@aluminum borate nanospheres. Transmission electron microscopy (TEM) characterization showed that the aluminum borate coating was uniform and dense, with a thickness of approximately 10 nm.

[0036] 3. Ti3C2T x Preparation of nanosheet dispersion

[0037] 1.0 g of Ti3AlC2 powder (MAX phase) was slowly added to 20 mL of 40% hydrofluoric acid solution, and the mixture was magnetically stirred and etched at 35 °C for 24 hours. After the reaction was completed, the mixture was repeatedly centrifuged and washed with deionized water until the pH of the supernatant was >6, yielding multilayer Ti3C2T. x Precipitation. Take 100 mg of multilayer Ti3C2T. x Dispersed in 100 mL of deionized water, the mixture was ultrasonically exfoliated in an ice-water bath for 1 hour under argon protection (power 300 W, on / off cycle 2s / 2s). Subsequently, it was centrifuged at 3500 rpm for 30 minutes, and the supernatant was collected, which is the monolayer or few-layer Ti3C2T. xThe nanosheet dispersion had a concentration of approximately 0.8 mg / mL. Atomic force microscopy (AFM) characterization showed that the nanosheets were approximately 2.5 nm thick and had a lateral dimension of approximately 1–3 μm.

[0038] 4. Barium sulfate@aluminum borate / Ti3C2T x Assembly of composite powders

[0039] Take 50 mg of dried barium sulfate@aluminum borate nanospheres and ultrasonically disperse them in 50 mL of deionized water. Under magnetic stirring, slowly add the dispersion dropwise to 250 mL of Ti3C2T x Nanosheet dispersion (containing approximately 200 mg Ti3C2T) x After the addition was complete, stirring continued for 6 hours. This allowed barium sulfate@aluminum borate core-shell nanospheres to deposit on Ti3C2T using electrostatic attraction and hydrogen bonding. x Nanosheet surface. Finally, the composite product was filtered, washed with deionized water, and vacuum dried at 60℃ to obtain the final barium sulfate@aluminum borate / Ti3C2T. x Composite powder (labeled BAB / Mxene). Scanning electron microscopy (SEM) shows that core-shell nanospheres are uniformly loaded on MXene sheets without obvious agglomeration.

[0040] Comparative Example 1: Pure Ti3C2T x powder

[0041] Take an equal amount of Ti3C2T prepared in step 3 above x The dispersion was directly filtered and dried to obtain pure Ti3C2T. x powder.

[0042] Comparative Example 2: Physically Mixed Samples

[0043] 50 mg of barium sulfate@aluminum borate nanospheres were mixed with 200 mg of pure Ti3C2T x The powder was simply physically mixed in a mortar for 10 minutes to obtain a physically mixed sample (labeled as BAB+Ti3C2T). x ).

[0044] Example 2: Preparation and Performance Testing of Epoxy Resin Composite Materials

[0045] 1. Preparation of composite materials

[0046] The BAB / Mxene composite powder prepared above and pure Ti3C2T from Comparative Example 1 were used together. xThe powder and the physically mixed powder of Comparative Example 2 were added to commercially available epoxy resin (brand name E-51) at a total filler content of 3 wt%. The specific process was as follows: the filler and epoxy resin prepolymer were mixed at 60°C by mechanical stirring and ultrasonic treatment for 30 minutes, then the curing agent (polyetheramine D230, epoxy resin to curing agent mass ratio of 100:32) was added, and after thorough stirring, vacuum degassing was performed. The mixture was then injected into a mold and cured by programmed temperature rise (80°C / 2h + 120°C / 2h) to obtain standard test strips.

[0047] 2. Mechanical property test results

[0048] Effect analysis: The BAB / Mxene composite powder prepared in this invention has a significantly better reinforcing and toughening effect on epoxy resin than pure Ti3C2T. x Compared with the physically mixed sample, the improvement in various properties such as tensile strength and flexural strength (38.2%-41.9%) reached or exceeded that of the physical mixture (BAB+Ti3C2T). x The increase in impact strength (+40.5%) is twice that of physical mixing (+16.3%), proving that it is not a simple additive effect, but a qualitative leap. In particular, the toughening effect is particularly outstanding, with the impact strength increase (+40.5%) far exceeding that of physical mixing (+16.3%), indicating that the structure has a unique advantage in resisting crack initiation and propagation. This is attributed to its unique core-shell-lamellar structure: (1) the rigid barium sulfate@aluminum borate core-shell spheres serve as efficient stress bearing and dispersion points; (2) the MXene lamellars serve as a flexible two-dimensional network, transferring the load to the core-shell spheres and inhibiting crack propagation through strong interfacial bonding force; (3) the strong interfacial bonding formed by in-situ assembly (superior to physical mixing) ensures the effective transfer of stress from the matrix to the filler.

[0049] Performance indicators Pure epoxy resin <![CDATA[Add 3% Ti3C2T x > <![CDATA[Add 3% BAB + Ti3C2T x (physical mixture)]]> Add 3% BAB / Mxene (this invention) Tensile strength (MPa) 65.2 ± 3.5 70.1 ± 4.1 (+7.5%) 78.8 ± 3.8 (+20.9%) 92.5 ± 4.5 (+41.9%) Bending strength (MPa) 98.7 ± 5.2 105.3 ± 6.0 (+6.7%) 118.6 ± 5.7 (+20.2%) 136.4 ± 6.3 (+38.2%) Impact strength (kJ / m²) 15.3 ± 1.2 16.0 ± 1.3(+4.6%) 17.8 ± 1.4 (+16.3%) 21.5 ± 1.5 (+40.5%)

[0050] Flame retardant performance test results (micro calorimeter, MCC)

[0051] sample Peak heat release rate (PHRR, W / g) Total heat release (THR, kJ / g) Carbon residue (800℃, wt%) Pure epoxy resin 512 ± 15 28.5 ± 1.2 3.2 ± 0.5 <![CDATA[Add 3% Ti3C2T x > 468 ± 18(-8.6%) 26.8 ± 1.1(-6.0%) 9.5 ± 0.8 <![CDATA[Add 3% BAB + Ti3C2T x > 425 ± 16(-17.0%) 25.1 ± 1.0(-11.9%) 14.3 ± 1.0 Add 3% BAB / Mxene 358 ± 14(-30.1%) 22.4 ± 0.9(-21.4%) 22.8 ± 1.2

[0052] Effect Analysis: The BAB / Mxene composite powder of the present invention exhibits the best flame retardant synergistic effect on epoxy resin. In all key flame retardant parameters, its improvement is far greater than that of single fillers and physical mixtures. In particular, the PHRR is reduced by 30.1%, which is the core indicator for measuring fire hazard, indicating that the combustion intensity of the composite material is significantly weakened. The BAB / Mxene composite powder of the present invention exhibits outstanding char-forming ability, with the char residue rate increased to 22.8%, which is more than 7 times that of pure epoxy resin and far higher than that of single fillers and physical mixture samples. This indicates that the composite powder of the present invention constructs an extremely effective thermal stability barrier in the condensed phase. Its mechanism is as follows: (1) The aluminum borate shell melts at high temperature to form a glassy protective layer, covering the polymer surface and isolating oxygen and heat; (2) The MXene sheets form a dense physical barrier in the matrix, effectively delaying the transmission of combustible gases and heat; (3) The barium sulfate core is stable at high temperature and, together with the formed char layer, plays a skeletal support role, preventing the char layer from cracking. The synergistic effect of these three factors significantly reduces combustion intensity and greatly increases high-temperature char residue, demonstrating the high efficiency of its condensed phase flame retardant properties.

[0053] Therefore, the barium sulfate@aluminum borate / Ti3C2T of the present invention x This composite powder, through its ingenious "core-shell-lamellae" structural design, exhibits superior mechanical reinforcement and highly efficient flame-retardant synergistic properties when added to a polymer matrix (such as epoxy resin). This composite powder successfully integrates reinforcement, toughening, and flame-retardant functions, providing an ideal functional filler solution for the preparation of high-performance, high-safety polymer composite materials.

[0054] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A barium sulfate@aluminum borate-Mxene composite powder, characterized in that, The composite powder has a core-shell-lamellar composite structure; barium sulfate nanospheres form the core, and aluminum borate layers are uniformly coated on the surface of the barium sulfate nanospheres to form a core-shell structure of barium sulfate@aluminum borate nanospheres; the barium sulfate@aluminum borate nanospheres are uniformly deposited and fixed on the surface of two-dimensional layered Mxene nanosheets.

2. The barium sulfate@aluminum borate-Mxene composite powder according to claim 1, characterized in that, The barium sulfate nanospheres have a particle size of 80-200 nm.

3. The barium sulfate@aluminum borate-Mxene composite powder according to claim 1, characterized in that, The thickness of the aluminum borate layer is 5-20 nm.

4. The barium sulfate@aluminum borate-Mxene composite powder according to claim 1, characterized in that, The Mxene nanoplatelets are Ti3C2T x having a thickness of 1-10 nm and a platelet planar size of 0.5-5 μm.

5. The barium sulfate@aluminum borate-Mxene composite powder according to claim 4, characterized in that, The Ti3C2T x T in x It is one or more of the surface terminating groups of -OH, -O, -F or -Cl.

6. A method for preparing barium sulfate@aluminum borate-Mxene composite powder as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Barium sulfate nanospheres were synthesized using a precipitation method; S2. Disperse the barium sulfate nanospheres obtained in step S1 in a solvent, add an aluminum source and a boron source, and coat the surface of the barium sulfate nanospheres with an aluminum borate layer through in-situ reaction to obtain barium sulfate@aluminum borate core-shell nanospheres. S3. Ti3C2T x nanosheet dispersion prepared by a liquid exfoliation method x The thickness of the Ti3C2T nanosheet is 1-10 nm, and the in-plane dimension of the sheet is 0.5-5 μm. S4. Combine the barium sulfate@aluminum borate core-shell nanospheres obtained in step S2 with the Ti3C2T nanospheres obtained in step S3. x The nanosheet dispersion was mixed to deposit and immobilize the barium sulfate@aluminum borate nanospheres on Ti3C2T. x The surface of the nanosheets was subjected to solid-liquid separation and drying to obtain the barium sulfate@aluminum borate / Mxene composite powder.

7. The method for preparing barium sulfate@aluminum borate-Mxene composite powder according to claim 6, characterized in that, In step S2, the aluminum source is aluminum nitrate, aluminum chloride, or aluminum isopropoxide; the boron source is boric acid, boron oxide, or sodium borate.

8. The method for preparing barium sulfate@aluminum borate-Mxene composite powder according to claim 6, characterized in that, In step S2, the in-situ reaction is a hydrothermal method or a sol-gel method, with a reaction temperature of 120-200℃ and a reaction time of 2-24 hours.

9. The method for preparing barium sulfate@aluminum borate-Mxene composite powder according to claim 6, characterized in that, In step S3, the liquid phase stripping method includes: reacting Ti3AlC2 powder in an acidic etching solution containing fluoride to selectively etch away the aluminum layer, thereby obtaining a multilayer Ti3C2T x Subsequently, the multilayer Ti3C2T x The Ti3C2T was obtained by intercalation and exfoliation in a polar solvent. x Nanosheet dispersion.

10. The method for preparing barium sulfate@aluminum borate-Mxene composite powder according to claim 9, characterized in that, The fluoride-containing acidic etching solution is an aqueous solution of hydrofluoric acid, a mixed solution of lithium fluoride and hydrochloric acid, or an aqueous solution of ammonium fluoride; the polar solvent is water, N,N-dimethylformamide, isopropanol, or propanol. In step S4, the barium sulfate@aluminum borate core-shell nanospheres and Ti3C2T x The mass ratio of the nanosheets is 1:10 to 10:1; the mixing method is stirring, ultrasonication, or a combination of both.